APPLICATION OF CREDIT DISTRIBUTION FOR CORPORATE BUSINESS SEGMENTS AT PT. BALI REGIONAL DEVELOPMENT BANK - Febriyanti, Ni Kadek Rika; Wirsa, I Nengah (LPPM Univ. Ibn Khaldun Bogor, 2024)
Corporate Credit is one of the sections of BPD Bali, corporate banking is frequently also referred to as business banking, comprising areas of banking connected to corporate services. Corporate banking is a key profit center for as big companies of banks, but corporations are the originator of the largest client loans, corporations corporations are also a frequent source of write-offs for loans that have deteriorated. The sector taken by corporate banking normally serves a broad range, ranging from small and medium companies (SMEs) to giant corporate categories with billions in sales and offices nationwide. The issues encountered by Bank BPD Bali in the credit sector include how to implement credit distribution and the constraining factors for credit distribution at Bank BPD Bali. The purpose of this study is to find out how the application of credit distribution for the corporate business segment at PT. Bali Regional Development Bank and to find out the inhibiting factors for applying credit distribution for the corporate business segment at PT. Bali Regional Development Bank. That means Bank BPD Bali may utilize this study as an assessment material for the inhibiting factors that restrict the spread of credit.